Syifa' dan Dawa': Kajian Fungsi Al-Qur'an sebagai Obat - Husni, Muhammad; Anggraini, Yuliza (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to explain the Qur'an as a healer/medicine which is taken from the verses of the Qur'an which states that the Qur'an is a syifa'. This research is a literature study using the thematic interpretation method by collecting verses that declare the Qur'an as syifa'. The source of the data is referring to the Qur'an and interpretations analyzed using a linguistic approach. The results of this study found that linguistically the word syifa' can be directed to physical and spiritual diseases. The Qur'an as a syifa’ is more aimed at spiritual diseases that can sometimes have an impact on the body. It is possible that with blessings and fadhilah (virtues) the verses of the Qur'an can be healed physically by certain people who are desired by Allah swt so that the Qur'an can function as a syifa' as well as a dawa'. This research is different from previous studies that state that the Qur'an is only syifa for spirituality, not as a dawa' or as syifa' as well as dawa' for various kinds of physical diseases that apply in general.